Air-Drill With Accelerometer And Microphone For Composite Drilling Application - Wei Tong, Koh (Universiti Sains Malaysia, 2022)
Impaired dimensional accuracy and assembly tolerance due to tool wear could leads to serious problem such as part dismissals in substantial amount on the structure of aircraft. To make sure that drilled holes in composite materials are of good quality from various aspects, current practice in the industries was the disposal of the drill bits after it is being used for a predetermined number of cycles. However, this leads to wastage of some of the expensive drill bit which can still produce holes without delamination even though it has been used for predetermined number of cycles. To monitor the tools condition, researchers have conduct various experiment to correlate tool wear with process variables such as cutting force, thrust force, vibrations, spindle current, acoustic emission etc. In this research, the effect of sharpness of drill bits on vibrations of air drill, sound produced during drilling and quality of holes produced will be studied. In this experiment, 3 accelerometers have been attached on locations near the spindle, at the middle and near the handle of air drill to measure the vibrations of the air drill. Microphone was placed about 1 meter away from the jig and the sounds produced during drilling process were collected. The vibrations of air drill and sound produced during drilling with different conditions of drill bit are analysed and compared. The result shows that vibrations measured by accelerometer placed nearest to the spindle are most sensitive to change in condition of drill bit. For CFRP plate, maximum amplitude of air drill vibration increases with condition of air drill in order: sharp, no drill bit, blunt, and chipped off. For GFRP plate, maximum amplitude of air drill vibration increases with condition of air drill in order: no drill bit, blunt, chipped off and sharp. Other than that, the fast Fourier Transform of the vibration signals from this accelerometer shows that there was a unique set of frequencies with significant peaks with different conditions of drill bits.